Plasma levels of n-3 fatty acids and risk of coronary heart disease among Japanese: The Japan Public Health Center-based (JPHC) study. (May 2018) - ,; Tsugane, S.; Sawada, N.; Iwasaki, M.; Sasazuki, S.; Yamaji, T.; Shimazu, T.; Goto, A.; Hidaka, A.; Hanaoka, T.; Ogata, J.; Baba, S.; et al.
Abstract: Background and aims: Higher intake of fish or n-3 polyunsaturated fatty acids (PUFAs) has been associated with reduced risk of coronary heart disease (CHD). However, it is unclear whether increased blood levels of n-3 PUFAs are associated with reduced risk of CHD in the Japanese population. Methods: The relationship between circulating levels of n-3 PUFAs (eicosapentaenoic acid + docosapentaenoic acid + docosahexaenoic acid) and risk of CHD was examined in a nested case-control study among participants in the Japan Public Health Center (JPHC)-based Study Cohort. Plasma n-3 PUFA phospholipid levels were measured at baseline by gas chromatography in 209 cases with CHD and 418 controls matched for sex, age, date of blood draw, time elapsed since last meal before blood collection, and study location. The CHD cases (n = 209) comprised 168 cases of myocardial infarction and 41 of sudden cardiac death, otherwise classified as 157 non-fatal and 52 fatal coronary events, respectively. Mean duration of follow-up was 13.5 years. Results: Multivariate conditional logistic analysis showed no significant association between n-3 PUFAs and risk of total CHD. The odds ratio (OR) for the highest versus lowest quartiles of plasma n-3 PUFAs was 0.79 (95% confidence interval [95% CI]: 0.41–1.51, p for trend = 0.51). Subtype analysis of CHD revealed that the multivariate ORs for the highest versus lowest quartiles for n-3 PUFAs were 0.91 (95% CI: 0.43–1.89, p for trend = 0.90) for myocardial infarction, 0.08 (95% CI: 0.01–0.88, p for trend = 0.04) for sudden cardiac death, 0.89 (95% CI: 0.42–1.89, p for trend = 0.97) for nonfatal coronary events, and 0.12 (95% CI: 0.02–0.75, p for trend = 0.03) for fatal coronary events. Conclusions: Plasma n-3 PUFA levels were not associated with risk of total CHD but were inversely associated with risks of sudden cardiac death and fatal coronary events among middle-aged Japanese individuals. Highlights: We have conducted a nested case-control study in a Japanese cohort. Plasma n-3 PUFAs were not associated with risk of overall coronary heart disease. Plasma n-3 PUFAs were associated with reduced risk of sudden cardiac death. Plasma n-3 PUFAs were associated with reduced risk of fatal coronary events.